Inversión pública y el desarrollo económico de la región Loreto en el periodo 2018-2022 - Fernandez Vasquez, Sonia Lily (2024)
The title of the research is "Public Investment and Economic Development of the Loreto Region during the Period 2018-2020", and its main objective is to examine the relationship between public investment and economic growth in said region during the aforementioned period. The variables studied are the Gross Value Added, considered as the dependent variable, and public investment, identified as the independent variable, covering the years 2018 to 2022. The theoretical framework supports the importance of public investment and its relationship with economic development. . After processing and analyzing the data collected, it is observed that both the Gross Domestic Product and public investment show an upward trend. This indicates a positive correlation, of r= 0.989343216 and R² = 0.9788, where both variables experience a proportional increase each year. In summary, the results of the analysis support the assertion that public investment positively influences the economic development of the Loreto region during the period from 2018 to 2022.